Multicultural Democratic and Tolerant: Qur'anic Perspectives and Islamic Education at the Universitas Muhammadiyah Surakarta - Abdullah Mahmud (Solo Universal Journal of Islamic Education and Multiculturalism, 2023)
The purpose of this study is to analyze the concepts of multicultural Democratic and Tolerant in the Qur'an and Islamic Education. This theme is motivated by the values of tolerance such as the prohibition of denouncing the gods of other religions, the prohibition of degrading the dignity of people of other religions, being able to communicate with followers of other religions, freedom of religion, the prohibition of forcing others to adhere to a religion, beliefs, religious laws, or moral laws that we believe in, not hating followers of other religions, and always huznudzan against them, and acknowledging the existence of other religions. This type of research is a field study, with data obtained through observation and interviews. The results of the study concluded that Democratic and Tolerant multicultural values in Islamic learning can be categorized into three learning models: 1. Baitul Arqam: semester 1-2 (for Muslim students); 2. Classical Learning: semesters 1-2 (non-Muslim students only); 3. Classical Learning: semester 3-4 (for Muslim and non-Muslim students). After in-depth research, it was found that the various multicultural Democratic and Tolerant values mentioned above are by learning the Islamic Education learning model at the University of Muhammadiyah Surakarta.